Analysis of Recurrence Management in Patients Who Underwent Nonsurgical Treatment for Acute Appendicitis. Issue 12 (March 2016) - Liang, Tsung-Jung; Liu, Shiuh-Inn; Tsai, Chung-Yu; Kang, Chi-Hsiang; Huang, Wei-Chun; Chang, Hong-Tai; Chen, I-Shu
Abstract : Abstract: The recurrence rate for acute appendicitis treated nonoperatively varies between studies. Few studies have adequately evaluated the management of these patients when appendicitis recurs. We aimed to explore the recurrence rate and management of patients with acute appendicitis that were first treated nonoperatively. We identified patients in the Taiwan National Health Insurance Research Database who were hospitalized due to acute appendicitis for the first time between 2000 and 2010 and received nonsurgical treatment. The recurrence and its management were recorded. Data were analyzed to access the risk factors for recurrence and factors that influenced the management of recurrent appendicitis. Among the 239, 821 patients hospitalized with acute appendicitis for the first time, 12, 235 (5.1%) patients were managed nonoperatively. Of these, 864 (7.1%) had a recurrence during a median follow-up of 6.5 years. Appendectomy was performed by an open and laparoscopic approach in 483 (55.9%) and 258 (29.9%) patients, respectively. The remaining 123 (14.2%) patients were again treated nonsurgically. Recurrence was independently associated with young age, male sex, percutaneous abscess drainage, and medical center admission by multivariable analysis. In addition, age <18, a (CCI) <2, medical center admission, and a longer time to recurrence were correlated with using laparoscopy to treat recurrence. Neither type of appendicitis, percutaneous abscess drainage, nor length of first time hospital stay had an influence on the selection of surgical approach. In conclusion, a laparoscopic appendectomy can be performed in recurrent appendicitis cases, and its application may not be related to previous appendicitis severity.